Prayang Innovation Technology on Capture Results - Huda, Samsul; Naviah, Siti; Habibah, Natasya (Fakultas Perikanan dan Kelautan Universitas Riau, 2020)
Prayang is traditional fishing gear, a prohibition on the use of cantrang fishing gear by the Ministry of Maritime Affairs and Fisheries (KKP) requires an alternative replacement fishing gear, considering that the condition of the Java sea waters is already overfished. The study aims to determine the effect of using different color lights on prayang fishing gear on catches. The research method is an experiment by applying